2002
DOI: 10.1017/s0142716402004010
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of expressive vocabulary to frequency of reading and television experience among bilingual toddlers

Abstract: This study investigated the relationships of expressive vocabulary size with frequency of being read to and frequency of watching television among 64 bilingual 21-to 27-month-old children from homes in which Spanish and English were spoken. The frequency of being read to in each language was related positively with expressive vocabulary size in the same language, and the relationships were significant even when taking the children's age and overall exposure to each language into account. The frequency of watch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
106
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 20 publications
(43 reference statements)
15
106
0
4
Order By: Relevance
“…Social interactions and experiences in language of care have been shown to influence language learning and literacy skills of children exposed to two languages (Eilers, Pearson, & Cobo-Lewis, 2006;Patterson, 2002;Patterson & Pearson, 2004;Pearson, 2007;Tabors & Snow, 2001;Verhoeven, 2006). The same was true for the bilingually reared children in our study.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Social interactions and experiences in language of care have been shown to influence language learning and literacy skills of children exposed to two languages (Eilers, Pearson, & Cobo-Lewis, 2006;Patterson, 2002;Patterson & Pearson, 2004;Pearson, 2007;Tabors & Snow, 2001;Verhoeven, 2006). The same was true for the bilingually reared children in our study.…”
Section: Discussionsupporting
confidence: 72%
“…Some evidence exists that frequency of social interactions, shared engagements with caregivers at home and day care, and joint activities with siblings and peers promote bilingual development (Pearson, 2007;Tabors & Snow, 2001;Verhoeven, 2006). Language-specific relations between frequency of joint picture-book reading and vocabulary size have been found already among 2-yearold Spanish-English bilinguals, even after controlling for amount of exposure (Patterson, 2002). Leseman and van Tuijl (2006) report that, in addition to the dominant language at home, frequency of joint reading well before school entry was related to Dutch vocabulary scores and oral text comprehension at 5 and 6 years of age, but not to phonological skills and PWM span.…”
Section: Exposure To Two Languages Influences Acquisition Of Literacymentioning
confidence: 99%
“…Exposure to non-dominant language at home environments may have little or no influence on production of error patterns in bilingual children, if the source of exposure to the non-dominant language is the parents who are not dominant in that language and therefore are not able to provide a robust model for bilingual children to learn and differentiate phonological systems [61,62]. In addition, the literature suggests that shared language experiences such as book reading are supportive of language development [63,64]. Mere exposure to language(s), reflected in language dominance, may not impose significantly on learning phonemic contrasts and reorganisation of phonological systems [e.g.…”
Section: Factors Influencing Error Production In Bilingual Childrenmentioning
confidence: 99%
“…Regarding quantity, Patterson (2002) found that the frequency of shared storybook reading in Spanish was positively and significantly related to Spanish expressive vocabulary size in bilingual toddlers. Multiple exposures to storybooks are important for young children acquiring a second language (Espinosa, as cited in Cohen et al 2012;Collins 2010).…”
Section: Shared Storybook Reading For Dlls; Quantity Quality and Efmentioning
confidence: 98%